KARAKTERISASI DAN UJI AKTIVITAS ASAP CAIR TERHADAP KANDUNGAN PROKSIMAT IKAN TERI (CHARACTERIZATION AND ACTIVITY OF LIQUID SMOKE ON PROXIMATE CONTENTS OF ACHOVY FISH) - Nita Wahyu Pratama; Mega Sari J Sofiana; Anthoni B Aritonang (Indonesian Journal of Pure and Applied Chemistry, 2021)
Coconut shell liquid smoke has been made from coconut shells by pyrolysis method at a temperature of 150 °C for 4 hours. Liquid smoke purified by adsorption using activated charcoal. The test results showed that activated charcoal could bring down the conciseness to become odourless and the color of liquid smoke from dark chocolate to yellowish-brown. The composition of the liquid smoke compound was determined by using the Gas Chromatography-Mass Spectrophotometer (GC-MS) consisting of 33.60% methylamine-D2 and 31.14% acetic acid as the dominant compounds. A solution of liquid smoke in water (6.0% v / v) was used for activity testing to the content of proximate by immersing fresh anchovy at room temperature with closed conditions for seven days. The results of the proximate test observed as follows: the water content tended to decrease, the highest on day 1 (11.56%) and the lowest on the 7th day (7.38%), the ash content tends to increase, the highest on the 7th day (9, 76%) and the lowest on the 1st day (6.52%), the fat content tends to increase, the highest on the 7th day (20.19%) and the lowest on the 1st day (9.72%) and the protein content is an increase, namely the highest on the 7th day (14.02%) and the lowest on the 1st day (10.20%). The water content decrease caused the ash content was increased as an indication of an enhancement in mineral content in the anchovy sample. Likewise, the water content decrease caused the higher fat content. Based on the results, it can be concluded that the liquid smoke produced from coconut shells purified by the activated charcoal is very promising as a foodstuffs preservative.